2009
DOI: 10.1021/bm801514x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking and Subcellular Distribution of a Large Array of HPMA Copolymers

Abstract: The basic physicochemical properties that determine the distribution and fate of synthetic macromolecules in living cells were characterized using fluorescently labeled HPMA (N-(2-hydroxypropyl)methacrylamide) copolymers. Twelve different classes of water-soluble copolymers were created by incorporating eight different functionalized comonomers. These comonomers possessed functional groups with positive or negative charges or contained short hydrophobic peptides. The copolymers were fractionated to create para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…The HPMA copolymers were prepared as described in [24]. The general copolymerization scheme, structures of comonomers used, and example of molecular weight profiles are shown in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
“…The HPMA copolymers were prepared as described in [24]. The general copolymerization scheme, structures of comonomers used, and example of molecular weight profiles are shown in Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, intracellular pH is more acidic, reaching 5.0 in endosomes and lysosomes (32). Such differences in pH throughout the body would permit these micelles to control the conditions of drug release in various locations differentially (33,34). DOX, a widely used anticancer drug, is used in this study as a model drug because it has a ketone group at its C13 position and also possesses the spectrometric advantages over detection of color and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…As a conduit for non - biological macromolecules, the NPCs have been shown to transmit PEG-coated gold colloid particles 4–7 nm in diameter [55]. The basic physico-chemical properties that determine the distribution and fate of synthetic macromolecules in living cells were characterized using fluorescently-labeled HPMA copolymers [56]. Twelve different classes of water-soluble copolymers were created by incorporating eight different functionalized comonomers.…”
Section: Design Principles For Water-soluble Polymer-drug Conjugatesmentioning
confidence: 99%
“…HPMA copolymers containing amide-terminated phenylalanine-glycine (FG) sequences, analogous to those found in the NPC channel protein, demonstrated a potential to regulate import to the nuclear compartment. Kinetic analyses showed that 15 kDa copolymers containing GG FG , but not those containing GGL FG , peptide pendant groups altered the size-exclusion characteristics of NPC-mediated nuclear import [56]. One possible explanation is that the GGFG moieties were able to weakly bind to FG-domain crosslinks in a way that altered the dynamics of a putative nucleoporin hydrogel structure, whereas GGLFG peptides would be expected to bind more strongly and not allow a rapid transfer of crosslinks in the hydrogel-like structure of the nucleopore proteins [57].…”
Section: Design Principles For Water-soluble Polymer-drug Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation